PENGARUH UKURAN PERUSAHAAN, FEE AUDIT, AUDIT TENURE, DAN ROTASI AUDIT TERHADAP KUALITAS AUDIT - Feby Mardyanti; Praptiningsih Praptiningsih (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
This research was conducted to test the effect of variables of Company Size, Fee Audit, Audit Tenure, and Rotation audit on Audit Quality. The sample in this study amounted to 59 primary consumer sector companies listed on the Indonesia Stock Exchange for the period 2018-2020 which were selected based on purposive sampling methods and also referred to the selected criteria. The sample data was obtained by 59 companies with a total sample of 177. The quality of audits in the study was measured using a proxy of the size of a public accounting firm. The analysis technique used is logistic regression with a significance rate of 5%. The results showed that (1) The Size of the Company had a significant positive effect on audit quality (2) Fee Audit had a significant effect on audit quality (3) audit tenure had no significant effect Positive to Audit Quality (4) Audit Rotation has no effect on Audit Quality.